Sizing of a Hybrid Photovoltaic-Hydrokinetic Turbine Renewable Energy System in East Malaysia - Buswig, Yonis.M.Yonis; Norhuzaimin, Julai; Al-Khalid, Hj Othman; Azuka, Affam; Yi, Sy Sim; Wahyu Mulyo, Utomo (IEEE, 2020)
The difficulties faced in the extension of conventional grid electricity to remote locations elicit increased application of renewable energy (RE) sources in such locations. In locations that are in proximity to rivers or streams, microhydro hybrid RE systems (HRES) are employed. Similarly, hybrid photovoltaic (PV) /battery configurations exist. Unfortunately, micro-hydro turbines require a minimum height/head and expensive civil works during installation. Hydrokinetic turbines (HKTs) eliminate the height/head requirement and greatly reduce necessary civil work by generating electricity using the kinetic energy of water flow in a river or stream. This study used a software, Hybrid Optimization of Multiple Energy Resources (HOMER), to simulate and obtain the optimal size and configuration of a hybrid PV/HKT/Battery storage system for Kampung Git in East Malaysia. Techno-economic comparison of the system is done with a PV/Battery and a standalone diesel generator (DG) system. The levelized cost of energy (LCOE) and the total net present cost (NPC) are the primary indices used for comparison purposes. The optimal configuration from simulations has 89.9 kWp of PV, two 3.5 kW HKTs and 132 kWh of battery storage. Also, economic results obtained indicate that the LCOE of 1.21 RM/kWh and NPC of RM 1,431,000 for the PV-HKT-battery configuration bested those for the PV-battery and standalone DG systems by 165 % and 27 % respectively. This optimal configuration is more environmentally friendly and highlights the role of the HKT in reducing battery usage and wear in addition to achieving lower LCOE and NPC values.